PROSEDUR PENGGUNAAN ACCURATE ACCOUNTING SOFTWARE ATAS TRANSAKSI PEMBAYARAN HUTANG USAHA PADA PT. MEKKO METAL MINING - Amanda Nurfadillah (2023)
Liabilities that arise when there is a purchase transaction on credit for the smooth operation of the company. Called accounts payable or accounts payable. Procedures for outgoing cash/bank accounting information systems include purchase transactions, purchases of goods or services, receipts based on documents used such as invoices, tax invoices and letters of cooperation agreement. Accurate is an example of computer-based accounting information system software that is often used by several companies. The purpose of preparing the final project report is to provide information regarding the use of an accurate system in paying PT. Mekko Metal Mining's business debts. In this writing, some of the data and information obtained at the data collection stage were then processed using a qualitative descriptive analysis method. The accounting information system for the accounts payable payment cycle at Accurate begins through the stage of inputting transaction data in each of the modules that have been provided. Furthermore, the input results are automatically entered into the general ledger, as well as the subsidiary ledger for recording accounts payable. Transaction adjustments related to payment of accounts payable on Accurate are done manually and are automatically included in the Financial Statements.